Current approaches to metaphor analysis in discourse - Navarro, I. (Ignasi) (Applications of cognitive linguistics, 2019)
This volume takes up the challenge of surveying the present state of a variety of approaches to the identification, analysis and interpretation of metaphor across communication channels, situational contexts, genres and social spheres. It reflects three foremost trends of present metaphor research, namely the communicative approach, the cognitive modelling approach and the multimodality approach. These trends are considered as areas of research emerging on the ground of the Conceptual Metaphor Theory, initiated by Lakoff. The book intends to show their concomitances as well as mark their diversifying paths. The aim is to bring about and make apparent the many connections among assumingly different trends stemming from CMT. Whereas discrepancies between communicative and conceptual perspectives might seem irredeemable, the book emphasizes and claims that the background framework of CMT provides a solid foundation for collaboration and mutual influence. Consequently, the analysis of metaphor usage in context may provide insights for cognitive modelling proposals. The analysis of cognitive configuration of conceptual domains may, in turn, illuminate our understanding of communicative decisions in discourse. The integration of multimodal metaphor analysis puts forward the idea that diverse modal manifestations of metaphor reveal the symbiosis between communicative and cognitive stances. The various subject areas and methodologies illuminate the scene of current research in the field. The poignant contributions open far reaching avenues into the realm of human thought and discourse.